Enhancing the Performance of Novel Archimedes Spiral Hydrokinetic Turbines Utilizing Blade Winglets in Deep-Sea Power Generation for Autonomous Underwater Vehicles - Ke Song; Huiting Huan; Liuchuang Wei; Chunxia Liu (Drones)
Deep-sea exploration relies heavily on autonomous underwater vehicles (AUVs) for data acquisition, but their operational endurance is limited by battery constraints. The Archimedes spiral hydrokinetic turbine (ASHT), as a novel type of horizontal-axis hydrokinetic turbine, has emerged as a promising solution for the harnessing of localized energy in the deep sea to power AUVs. This study explores the application of winglets on an ASHT to enhance its performance through computational fluid dynamics (CFD). The analysis focuses on the effects of the winglet angle and height ratio on the power and thrust, as well as the pressure distribution and flow characteristics. The findings indicate that strategically designed winglets, particularly those with angles greater than 90° and larger height ratios, can significantly improve the ASHT’s performance. This enhancement can be attributed to the winglets’ capacity to effectively reduce tip loss and expand the turbine’s swept area, thereby enhancing power extraction. The optimal configuration, determined at a winglet angle of 135° and a height ratio of 12–14%, demonstrates significant enhancements, including a minimum increase of 12.0% in power efficiency compared to the original ASHT. However, the study also acknowledges potential challenges; winglets with larger angles and height ratios may lead to increased load fluctuations, which require careful structural considerations. This study provides valuable insights into the design and optimization of ASHTs for deep-sea power generation, thereby contributing to the advancement of sustainable energy solutions for AUVs.